REFLECTING ON THE ROLE OF THE LECTURER IN INVERTED CLASSROOM TEACHING SCENARIOS - Anja Pfennig (PUPIL: International Journal of Teaching, Education and Learning, 2026)
It has widely been reported that students` motivation and self-attentiveness increase when teaching students via “inverted classroom” teaching scenarios in a blended learning environment. Inverting the classroom is a method to encourage students to self-study the science and then take time to work on their questions and do extended hands-on lectures or exercises in class. Therefore, a sufficient number and variety of teaching material aiming at different learning skills of the students has to meet the diversity of the first year class as well as the overall learning outcome of the course. But, most important for succeeding in inverted classroom environments is to respond to the change of the role as a lecturer from in-front teaching to a more cooperative and collaborate way of teaching. Set-backs are common when starting this teaching method because despite the advantages there are many aspects that need to be taken into account, such as: what to do with unprepared students or easy questions where to go in class during group work. Only if these negative aspects are clear from the beginning and there are answers to problems arousing this teaching method will increase the fun of teaching and be of success for students as well as lecturers. In this practice paper, difficulties are named and possible ways of handling are suggested as the author is still in the procedure of professionalizing the teaching method.